ISOLATION AND CHARACTERIZATION OF CHITINOLYTIC PAENIBACILLUS SP. D10-2 FROM TROPICAL SHRIMP POND WASTE WATER - Prasetyo, Amrih (EM International Global Science Publication, 2016)
The purpose of this study was to obtain superior chitinolytic bacteria capable of degrading chitin from the waste water of tropical shrimp pond. The bacterium characterization was conducted to yield highactivity chitnase isolates. While bacterium identification was carried out based on morphology, physiology, biochemistry and molecular. Screening was performed by colloidal chitin agar medium incubated at 30°C, five days, and flasks were incubated in an orbital incubator shaker at 30°C and 150 rpm. The enzyme activity was measured at intervals for five days. The cultures were centrifuged at 10,000 g for 15 min at 4°C, and the enzyme solution (culture supernatant) was used for chitinase assay. The morphological, physiological and biochemical characteristic of the VITEK system. The 16SrRNA method was used to identify strain. Results of morphological identification, biochemical and molecular identified as Paenibacillus sp. D10-2 including the genus Bacillus. Showed chitinase activity in medium containing chitin as a carbon source. The enzyme chitinase produced by Paenibacillus sp. D10-2 chitinase contained 29.46 (U / mg protein). Chitinolytic bacteria Paenibacillus sp. are able to degrade chitin specifically into the monomer in the form of glucosamine. They are widely used in in the fields of agriculture, food and health industries.